Perkembangan Pemikiran Euthanasia terhadap Pengaturan Hukum di Indonesia (Perspektif Politik Hukum Pidana) - St Harun Pudjiarto (Fakultas Hukum Universitas Islam Indonesia, 2001)
The purpose of this articles to discuss about legal policy on euthanasia, especiaily in the formulation phase. In this case euthanasia has been drafted in the bill ofthe New Indonesian Penal Code, anditseems thai passive euthanasia canbe carried out. The analysis shows that such aprovision in the bill of the New Indonesian Penal Code is already true because it can temiinate the dilemma on the choice taken by doctors whichhas the same risk.